2019
DOI: 10.9734/ajocs/2019/v6i419005
|View full text |Cite
|
Sign up to set email alerts
|

Validated Stability Indicating HPTLC and UV-Spectrophotometric Techniques for the Determination of Avanafil

Abstract: Aims: To develop methods with complete validation according to ICH guidelines and to be applied for the determination of avanafil in pure form and in pharmaceutical formulation in the presence of its degradation products. Study Design: High performance thin layer chromatography (HPTLC) and different spectrophotometric methods (dual wavelength, first derivative, first derivative of ratio spectra and ratio difference are developed for simultaneous determination of avanafil in laboratory-prepared mixtures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It was found that our method is advantageous in various points. Regarding sensitivity, the developed approaches are more sensitive than the published methods [18–20, 22, 38, 39, 41, 46–49]. Furthermore, our method is the simplest and greenest approach for the analysis of the examined drugs in plasma samples.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was found that our method is advantageous in various points. Regarding sensitivity, the developed approaches are more sensitive than the published methods [18–20, 22, 38, 39, 41, 46–49]. Furthermore, our method is the simplest and greenest approach for the analysis of the examined drugs in plasma samples.…”
Section: Resultsmentioning
confidence: 98%
“…It has lower adverse effects and faster onset than other PDE5 inhibitors [26,27]. Several analytical methods have been reported for the estimation of AVA, such as chromatographic methods [28][29][30][31][32][33][34][35][36][37][38][39], spectrophotometry [38,39], and spectrofluorimetry [40][41][42].…”
Section: Ava 4-((3-chloro-4-methoxybenzyl)amino)-2-(2-(hydroxymethyl)mentioning
confidence: 99%
“…The best peak appeared at pH 6 and the scan rate was 100 mV s −1 . pH effect.-The effect of pH on the electrochemical analysis of AVA was investigated using 0.04 M BR buffers with different pH values (2)(3)(4)(5)(6)(7)(8)(9). It was found that the pH value of a solution affects the electrochemical behavior such as peak current and potential of the oxidation of AVA.…”
Section: Resultsmentioning
confidence: 99%
“…2 It is readily soluble in 0.1 M hydrochloric acid, non-water soluble, slightly soluble in ethanol and sparingly soluble in methanol. 2 Different studies for the estimation of AVA alone or in a mixture with other drugs were reported such as UV-vis spectrophotometry, [3][4][5][6] HPLC, 7-10 HPTLC 11 and fluorimetry. 12 Electroanalytical methods have many advantages compared to other traditional methods such as high sensitivity, low time-consuming, low detection limit, especially when using modified electrodes, relatively inexpensive and simple operations.…”
mentioning
confidence: 99%
“…Recently, AVA was co-formulated with DAP to treat impotence and premature ejaculation. Several techniques were reported for the estimation of AVA in drug products including spectrophotometry [5,6], HPLC [7][8][9], LC-MS/MS [10] and voltammetry [11]. Different studies were developed for the determination of DAP alone or in a combination with other drugs including UV-Vis spectrophotometry [12][13][14][15], HPLC [16][17][18][19][20][21][22], capillary electrophoresis [23,24], screen printed electrode [25] and potentiometric ion-selective electrodes [26].The analytical techniques for determination of AVA and DAP in binary mixtures were reported including spectrophotometry [27,28], HPLC [29,30], HPTLC [31] and fluorimetry [32].…”
Section: Introductionmentioning
confidence: 99%